The Relationship of Screen Time to the Incidence of Speech Delay in Children Aged 2-5 Years - Pebriana, Rauhil; Wahyudi, Iwan; Mastuty, Amalia (Balai Publikasi Indonesia, 2025)
: This study analyzes the relationship between screen time and the incidence of speech delay in children aged 2-5 years. The Alpha generation, which was born in 2010, is known as a smart generation because it grew up in the era of technology and the internet. However, excessive use of screen time can reduce social interaction and interfere with children's speech development. The method used was descriptive quantitative with a cross sectional approach, involving 60 respondents who were selected through purposive sampling and measured using questionnaires. The results showed that 19 respondents (52.8%) with high screen time intensity experienced speech delay, while 9 respondents (50.0%) with moderate intensity and 5 respondents (83.3%) with low intensity also experienced the same. The hypothesis test using Kendall's tau c yielded a p-value of 0.461 (p > 0.05), indicating no significant association between screen time and speech delay events. The conclusion of this study confirms that screen time does not have a significant effect on children's speech development in the region.